Improving Students’ Motivation and Speaking Skill Through Negotiated Materials Based on Current Syllabus at Grade XI Accounting of SMK.N 1 Pasir Pengaraian Rokan Hulu Riau - Rahayu, Pipit (Edu Research, 2012)
The purpose of this research was to improve the students’motivation and speaking skill through negotiated materials.Negotiated materials means that materiasl come from discussion by teacher and students and these negotiated materials which is based on their students’ study program (Accounting). Motivation means thosestudents’ effort plus desire in speaking activity or in other wordsstudents’ motivation in speaking. While speaking skill means that the capacity of the students to present their materials in front of the class.The participants of this research were the eleventh grade students of Accounting at SMKN 1 PasirPengaraianRokanHulu Riau. This class consisted of 38 students. One of the English teachers took part in this research as collaborator to assist the implementation of Negotiated Materials, particularly in observing the students’ activities in the teaching and learning process